Remittances, Total Factor Productivity And Economic Development in Africa. - Dzeha, G. C. (University of Ghana, 2017)
This study examines the implication of international migrants‘ remittance, total factor productivity (TFP) and economic development in Africa. It is based on three empirical papers. The first empirical chapter looks at the effect of international migrants‘ remittances on labour productivity and capital accumulation. In this study we conceptualise how remittances received in Africa could lead to labour productivity and capital accumulation. The study also tested the interactive effect of remittances and human capital on capital accumulation. The study employs a panel of twenty-five African countries across a twenty-three-year period (1990 – 2013) using the two-step generalised methods of moment estimator and finds that remittance promotes labour productivity. While the study does find evidence that remittances promote capital accumulation; it does show that the interactive effect of remittance and human capital largely impacts capital accumulation. Thus, remittance inflows only lead to capital accumulation if recipients are skilled and trained. The second paper examines the effect of international migrants‘ remittance on Total Factor Productivity (TFP) within sampled African countries. The study first employs the output based non-parametric Malmquist productivity index- Data Envelope Analysis in a macroeconomic context to segregate the component of TFP into technical change, efficiency and TFP growth. In this context, the real GDP is the output that is produced by the countries; while the physical capital stock and labour are the set of inputs. The study further investigates the consequence of migrants‘ remittances on each component of TFP by the use of the Seemingly Unrelated Regression estimation technique on a panel of twenty-three African countries across a twenty-three-year period (1990 – 2013). The study shows that international migrants‘ remittances, although received by households, are a valuable source of capital that increases technical change (innovation) and spurs the growth in total factor productivity, but does not encourage efficiency. Confirming that, there is no doubt that University of Ghana http://ugspace.ug.edu.gh viii innovation cannot happen without money, migrants‘ remittance inflows are very important and significant in enabling recipients to bring their ideas to life through innovation. Remittances increase recipient households‘ purchasing power and create opportunities by making it easier for recipients to acquire simple tools and equipment that promote productive investments and lead to increase in productivity growth directly. International migrants‘ remittance inflows, through official channels, make available huge capital inflows that change the dynamics of productive investments through innovation and growth in technology. Hence the repercussions are that there is the need for governments to create enabling and congenial economic environments that will increase remittance inflows. A congenial economic environment will create opportunities for remittance-recipients to put these monies into economic activities that have far-reaching effects and enhance living standards. The third paper also examines the effect of Total Factor Productivity (TFP) on human development contingent on the level of remittances in Africa. The study essentially employs the inequality-adjusted human development index as a proxy for human development in Africa and employs the system Generalised Methods of Moments (SGMM), with a set of data on a sample of twenty-one African countries over a five-year period (2010–2014) in a balanced panel. The findings of the study show that TFP has a negative effect on human development; meanwhile, human development is affected by remittances positively. However, the combined effect of TFP and remittances turns out to be positive, suggesting that countries that receive a high level of remittances are able to transform the negative impact of TFP on human development into a positive one. The implications are that, although remittances are received by households, their cumulative effect could drive total factor productivity to promote human development. As Africa‘s population continuous to grow astronomically, it becomes pragmatically assiduous for Africa to take advantage of its increasingly active population in the diaspora seeking greener pastures and sending remittances to transform its human development levels in education attainment, poverty alleviation and increasing life expectancy.
Keywords: international migrants; factor productivity (TFP); economic development; Africa; empirical chapter; capital accumulation; macroeconomic; Unrelated Regression; productivity